علم النفس الايجابي: تناول مفاهيمي - مصمودي, زيـن الديـن; باشا, فاتن ، (Sciences de l'Homme et de la Société, 2016)
يسعى علم النفس الايجابي من أجل تجويد الحياة النفسية من خلال الاهتمام بالمستوى الذاتي للفرد، والذي يرتبط بالخبرة التي لها قيمة مثل السعادة والرضا والارتياح، وهي قيم تتعلق بالزمن الماضي للفرد، كما يرتبط بالخبرة الذاتية والسعادة الانفعالية الحالية المرتبطة بالزمن الحاضر الذي يعيشه الفرد، إضافة إلى ارتباطه المتكامل بكل من بُعدي الأمل والتفاؤل بما يتعلق بزمن المستقبل.   Abstract : Positive psychology aims to improve the psychological life taking care personally of the individual that is linked to an experience that has a value such as happiness and contentment and satisfaction. Which are past-related values of the individual, and linked to personal experience and emotional happiness associated with this experienced by the person and its integrated relationship to the hope and optimism about the future.